Natural polymers for pharmaceutical applications. Volume 2, Marine- and microbiologically derived polymers - Nayak, Amit Kumar, 1979-; Hasnain, Md Saquib, 1984-; Pal, Dilipkumar, 1971- (Oakville, ON, Canada : Apple Academic Press, 2020)
Many polymers derived from various marine sources and microorganisms possess some important biological properties such as biocompatibility, biodegradability, and bioadhesivity that make them attractive as pharmaceutical excipients in various pharmaceutical dosage forms. Moreover, these polymers can be modified physically and/or chemically to improve their biomaterial properties. In this volume, Natural Polymers for Pharmaceutical Applications, Volume 2: Marine- and Microbiologically Derived Polymers, looks at how these polymers have been explored and exploited for pharmaceutical uses, such as in tablets, microparticles, nanoparticles, ophthalmic preparations, gels, emulsions, suspensions, etc. Some commonly used marine- and microbiologically derived polymers used as pharmaceutical excipients include alginates, agar-agar, gellan gum, carrageenan; chitosan, xanthan gum, and others. The book focuses on important recent advances from experts around the world on marine-derived polysaccharides and pharmaceutical applications of alginates, agar-agar, gellan gum, carrageenan, chitosan derivatives, xanthan gum.
Volume 2: Marine- and Microbiologically Derived Polymers 1. Marine-Derived Polysaccharides: Pharmaceutical Applications Dilipkumar Pal et al. 2. Pharmaceutical Applications of Alginates Amit Kumar Nayak et al. 3. Pharmaceutical Applications of Agar-Agar Md. Shahruzzaman et al. 4. Pharmaceutical Applications of Gellan Gum Shakti Nagpal et al. 5. Pharmaceutical Applications of Carrageenan A Papagiannopoulos and S. Pispas 6. Pharmaceutical Application of Chitosan Derivatives Fiona Concy Rodrigues, Krizma Singh, and Goutam Thakur 7. Pharmaceutical Applications of Xanthan Gum Subham Banerjee and Santanu Kaity
OCLC-licensed vendor bibliographic record.
Keywords: Polymers in medicine; Biopolymers; Pharmaceutical technology